Solitary glomangioma on the chin: A rare case report - Min-Woo Lee; Ju-Young Lee; Sung-Min Park (Oral and Maxillofacial Surgery Cases, 2022)
A 63-year-old man with a 2-year history of a slowly growing mass in the chin area was referred to the Department of Oral and Maxillofacial Surgery, Dankook University Dental Hospital. Physical examination revealed a 1.2 × 1.0 cm bluish mass in the middle of his chin, which was tentatively diagnosed as a hemangioma. Considering the size and location of the lesion, an excisional biopsy was performed under local anesthesia. Bleeding and other complications were not observed. The results of histopathological examination revealed glomangioma. This study aimed to report a case of solitary glomangioma arising in the chin, which is not the usual location of this tumor. To the best of our knowledge, this is the first report of a solitary glomangioma in the chin area in the oral and maxillofacial surgery literature.